Ceramic firedogs in central-southern Etruria between residential, sanctuary and ritual contexts (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2021)
A differenza degli alari metallici, che provengono quasi esclusivamente da contesti funerari, gli alari fittili in territorio etrusco sono attestati soprattutto dal Bronzo finale fino al V sec. a.C. e sono restituiti esclusivamente da contesti di abitato, votivi, e da santuari. Il presente contributo tenta di individuare una classificazione tipologica dei manufatti rinvenuti nell’Etruria tirrenica, prendendo in esame anche reperti inediti. In particolare, si individuano alcune fogge che sembrano giunte in Etruria in seguito a contatti tra l’area medio-danubiana dei Campi di Urne attraverso il tramite dell’Italia nord-occidentale. In contrast to metallic firedogs, found almost entirely in funerary contexts, ceramic firedogs are attested in the Etruscan territory especially from the Late Bronze Age until the V century B.C. These are found in settlements, votive contexts and sanctuaries. This paper tries to set up a typological classification of ceramic firedogs manufactured in Southern Etruria, both published as well as some unpublished finds. Certain types of firedogs, in particular, seem to proceed from cultural contacts with the Middle-Danube Urnfield culture, through the North-Western italic area.
Keywords: Firedogs; Etruria; Pottery; Instrumentum domesticum; Urnfield culture; Late Bronze Age; First Iron Age; Fireplace; Zoomorphic Protome